Digital Investment and Online Financial Markets: A Quantitative Case Study on Mutual Fund Investment Decisions by Millennials Using Blue Apps in Jakarta - Nurmala, Riska; Tomana, Josef; L. Tobing, Rangga; Sari, Kartika; Lestari, Nurul Khofifah; Marjohan, Masno (Lafadz Jaya Publisher, 2025)
The development of digital technology has driven significant changes in investment behavior, particularly among millennials. This study aims to analyze the influence of financial literacy, risk perception, and ease of use of applications on mutual fund investment decisions among millennials who use the Blue App in Jakarta. This study employs a quantitative approach using a survey method, involving 120 respondents selected through purposive sampling. The research instrument consists of a closed-ended questionnaire with a Likert scale, and the data was analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that financial literacy has a positive and significant effect on investment decisions, suggesting that the higher an individual's financial understanding, the more rational their investment decisions. Risk perception has a negative and significant effect, meaning that the higher the perceived risk, the lower the individual's tendency to invest. Meanwhile, the ease of use of the application was found to have a positive and significant influence on investment decisions, indicating that a good user experience encourages higher investment activity. This study has implications for application developers and financial institutions to improve financial literacy, minimize risk perception, and continue to refine application features to encourage increased digital investment participation among the younger generation.